2013
DOI: 10.3109/10428194.2013.819100
|View full text |Cite
|
Sign up to set email alerts
|

Significance of CD71 expression by flow cytometry in diagnosis of acute leukemia

Abstract: In this study we investigated the significance of CD71 (transferrin receptor 1, TfR-1) as a flow cytometric marker in the diagnosis of acute leukemia (AL). A total of 105 patients with AL were enrolled. Poorly differentiated acute myeloid leukemias (AMLs) (including minimally differentiated AML, AML without maturation, AML with maturation, acute myelomonocytic leukemia) tended to express high levels of CD71 on leukemic cells, while partially differentiated AML (including acute promyelocytic leukemia and acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
7
32
0
Order By: Relevance
“…Also Pande et al [33] found that the Majority of AMLs showed positivity for CD71, being positive in 84% of the cases while The CD71 positivity rate was only 30% in cases of B-ALL. Liu et al [28] found [28] and AMoL in our study had low CD 71% expression and MFI 19.5 (13.6 -25.7), 1.3 (1.3 -1.8) respectively similar to Liu et al . [28] .…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Also Pande et al [33] found that the Majority of AMLs showed positivity for CD71, being positive in 84% of the cases while The CD71 positivity rate was only 30% in cases of B-ALL. Liu et al [28] found [28] and AMoL in our study had low CD 71% expression and MFI 19.5 (13.6 -25.7), 1.3 (1.3 -1.8) respectively similar to Liu et al . [28] .…”
Section: Discussionsupporting
confidence: 76%
“…Liu et al [28] found [28] and AMoL in our study had low CD 71% expression and MFI 19.5 (13.6 -25.7), 1.3 (1.3 -1.8) respectively similar to Liu et al . [28] .…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations